Moderating Effects on the Relationship Between Accounting Comprehension and Local Government Financial Reporting - Jati, I Ketut; Kresnandra, Anak Agung Ngurah Agung; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 34 No 11 (2024), 2024)
This study examines the direct impact of accounting comprehension on the quality of financial reports and explores the moderating effects of the Internal Control System (SPI), Accounting Information System (AIS), Human Resource (HR) Competence, and Organizational Commitment on this relationship. The research focuses on employees in the finance and accounting divisions of 31 Regional Apparatus Organizations (OPD) within the Buleleng Regency Government. A purposive sampling technique was employed, yielding a sample of 90 respondents. Primary data were collected through questionnaires, and the data were analyzed using moderated regression analysis (MRA) with SPSS as the analytical tool. The findings indicate that accounting comprehension has a significant effect on the quality of financial reports. Furthermore, SPI, AIS, and HR Competence serve as moderating variables that strengthen this relationship. However, Organizational Commitment does not moderate the effect of accounting comprehension on financial reporting quality. Keywords: Financial Report Quality; Accounting Understanding; Internal Control System; Accounting Information System; Human Resources Quality